Kobiece narracje kryzysu. Doświadczenie żałoby w „Sorge” Aleksandry Zielińskiej - Joanna Szewczyk (Jednak Książki, 2022)
This article concerns Aleksandra Zielińska’s novel Sorge. The author focused on relationships beetwen women – mothers, daughters and sisters in perspective of women’s mourning and also uses cathegory of trauma, abnormal grief and unresolved grief. The author analyses Sorge as (post)pandemic reinterpretation of legend of Pied Piper of Hamelin and examines contemporary forms of mourning in perspective of social quarantines.